Finding Exact Bright Soliton Solutions for Vakhnenko-Parkes Equation with Time-Dependent Coefficients (Latakia University Journal -Basic Sciences Series, 2020)
The aim of this research is to present exact analytical bright soliton solutions for Vakhnenko-Parkes equation with time-dependent coefficients by using the solitary wave ansatz method. Conditions for existence of these solutions basing on the coefficients of the equation are presented. We find that the used method is efficient to obtain this kind of solutions for the partial differential equations.